Improved Locus‐Specific Database for OPA1 Mutations Allows Inclusion of Advanced Clinical Data. Issue 1 (1st December 2014) - Ferré, Marc; Caignard, Angélique; Milea, Dan; Leruez, Stéphanie; Cassereau, Julien; Chevrollier, Arnaud; Amati‐Bonneau, Patrizia; Verny, Christophe; Bonneau, Dominique; Procaccio, Vincent; Reynier, Pascal
<x xml:space="preserve">Abstract</x> Autosomal dominant optic atrophy (ADOA) is the most common inherited optic neuropathy, due to mutations in the optic atrophy 1 gene (OPA1) in about 60–80% of cases. At present, the clinical heterogeneity of patients carrying OPA1 variants renders genotype‐phenotype correlations difficult. We have developed a clinico‐biological database, aiming to add clinical phenotypes, including detailed ophthalmological and neurological data, related to OPA1 variants (http://opa1.mitodyn.org/). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>